1995
DOI: 10.1126/science.7824936
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RET as a Dominant Transforming Gene by Germline Mutations of MEN2A and MEN2B

Abstract: Multiple endocrine neoplasia types 2A and 2B (MEN2A and MEN2B) and familial medullary thyroid carcinoma are dominantly inherited cancer syndromes. All three syndromes are associated with mutations in RET, which encodes a receptor-like tyrosine kinase. The altered RET alleles were shown to be transforming genes in NIH 3T3 cells as a consequence of constitutive activation of the RET kinase. The MEN2A mutation resulted in RET dimerization at steady state, whereas the MEN2B mutation altered RET catalytic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
546
0
8

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 823 publications
(577 citation statements)
references
References 14 publications
23
546
0
8
Order By: Relevance
“…The activated RET constructs, but not the vector, pBabehygro, generated foci in NIH3T3 cells and caused neurite-like extensions in PC12 cells (data not shown). These results are identical to others (Asai et al, 1995;Califano et al, 1995;Santoro et al, 1995) Figure 5 (a) RNase protection analysis of cytoplasmic vs nuclear RET mRNA. The colon cancer cell line, RKO, serves as a negative control for RET mRNA.…”
Section: Ret Overexpression In Tt:draf-1:er Cellssupporting
confidence: 90%
“…The activated RET constructs, but not the vector, pBabehygro, generated foci in NIH3T3 cells and caused neurite-like extensions in PC12 cells (data not shown). These results are identical to others (Asai et al, 1995;Califano et al, 1995;Santoro et al, 1995) Figure 5 (a) RNase protection analysis of cytoplasmic vs nuclear RET mRNA. The colon cancer cell line, RKO, serves as a negative control for RET mRNA.…”
Section: Ret Overexpression In Tt:draf-1:er Cellssupporting
confidence: 90%
“…Gainof-function mutations of the RET gene have been associated with multiple endocrine neoplasia type 2 (MEN 2), an autosomal dominant inherited cancer syndrome (Mulligan et al, 1993), whereas loss-offunction mutations of RET have been associated with Hirschsprung disease (aganglionosis, HSCR), a frequent congenital intestinal malformation (1 in 5000 live births) characterized by the absence of neural crest-derived parasympathetic neurons of the hindgut (Edery et al, 1994;Romeo et al, 1994). In vitro, MEN 2-associated mutations lead to ligand-independent constitutive activation of RET kinase activity either through covalent dimerization of the receptor (MEN 2A) (Santoro et al, 1995) or through direct structural changes in its kinase domains (MEN 2B) (Songyang et al, 1995). In contrast, the mechanisms leading to the absence of intramural ganglion cells of the hindgut observed in HSCR remain incompletely understood.…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…Speci®cally, germline mutation at codon 918 (M918T) in exon 16 is associated with 495% of MEN 2B , which is characterized by a more severe form of MTC and phaeochromocytoma occurring at a young age and classic stigmata such as ganglioneuromatosis and a marfanoid habitus. Functional, biochemical and limited animal modelling studies have demonstrated that the RET mutations which characterize MEN 2 are capable of activation, sometimes in a constitutive manner, of the RET signalling pathway (Borrello et al, 1995;Ceccherini et al, 1997;Michiels et al, 1997;Pasini et al, 1997;Santoro et al, 1995). The MEN 2B-type mutation, M918T, has been shown to alter substrate speci®city (Borrello et al, 1995;Santoro et al, 1995;Songyang et al, 1995).…”
mentioning
confidence: 99%